Forecaster overconfidence and market survey performance - Richard Deaves; Jin Lei; Michael Schröder (Frankfurt School of Finance & Management, 2015)
We document using the ZEW panel of German stock market forecasters that weak forecasters tend to be overconfident in the sense that they provide extreme forecasts and their confidence intervals are less likely to contain eventual realizations. Moderate filters based on forecast accuracy over short rolling windows are somewhat successful in improving predictability. While poor performance can be due to various factors, a filter based on a prior tendency to provide extreme forecasts also improves predictability.
Keywords: G02; G17; 330; Overconfidence; Forecasting Performance; Stock Market